Mechanism-guided drug development and treatment for liver fibrosis: a clinical perspective - Zeng, Xiangchang; Huang, Deliang; Zhu, Zhibin; Cai, Qingxian; Yang, Yang; Lu, Hongzhou; Chen, Jun (Frontiers in Pharmacology, 2025)
Liver fibrosis is a common response to chronic liver injury due to multiple etiologies and plays a crucial in the progression of chronic liver disease to cirrhosis, hepatocellular carcinoma, and other liver-related clinical outcomes. Currently, available treatments to block liver fibrosis are designed to eliminate the underlying causes of liver disease. The lack of truly effective drugs to regress or reverse fibrosis is a major unmet clinical need. In this context, this article briefly describes the pathological process of hepatic fibrosis and focuses on reviewing the progress of clinical studies on mechanism-based anti-fibrotic drug development and therapy, highlighting that the positive effect of thyroid hormone receptor-β (THR-β) analogs, fibroblast growth factor 21 (FGF21) analogues, Glucagon-like peptide 1 receptor (GLP-1R) agonists, pan-peroxisome proliferator-activated receptor (pan-PPAR) agonists, fatty acid synthase (FASN) inhibitors, and hydronidone in reducing liver fibrosis caused by specific etiologies. Moreover, multi-pathway guided combination therapy or traditional Chinese medicine demonstrate significant advantages in combating liver fibrosis. Finally, new technologies and approaches affecting the clinical development of anti-hepatic fibrosis drugs were discussed.